Modified cell penetrating peptides for efficient gene transfer in vitro and in vivo - Osman, Gizem (2017)
The efficient delivery of DNA is of great importance for therapeutic applications such as gene therapy, gene-editing and cell programming. However, the phospholipid bilayer of the cell membrane acts as an impenetrable barrier to nucleic acids and therefore a gene must be coupled to an intracellular delivery vector for efficient transfection. An optimal gene carrier must be able to deliver DNA to the entire cell population, transfect cells efficiently, be serum-resistant and cause minimal cytotoxicity. The majority of non-viral transfection strategies fall short of meeting these requirements, limiting their therapeutic utility. Cell penetrating peptide (CPP)-based vectors have been extensively used for the intracellular delivery of DNA, however low transfection efficiency has inhibited their clinical adoption. GET peptides (i.e. CPPs functionalised with heperan sulphate glycosaminoglycan (HS GAG) cell targeting ligands) have demonstrated 2 orders of magnitude improved delivery compared to unmodified CPPs. They overcome some of the challenges in non-viral DNA delivery by exhibiting minimal cytotoxicity and superior gene transfer. Additionally, PEGylated GET/DNA NPs were engineered with tuneable physiochemical properties for widespread and efficient transfection in mouse lung models. “Mucus penetrating” PEG GET NPs exhibited enhanced safety profiles and significantly better in vivo transfection efficiency compared to polyethylenimine (PEI) complexes. This work presents efficient GET-peptide mediated in vitro and in vivo transfection of DNA as a novel approach for gene therapy treatment.